Teaching planning or sentence-combining strategies: Effective SRSD interventions at different levels of written composition - Teresa Limpo (2013)
This study tested the effectiveness of two strategy-focused interventions aimed at promoting fifth and sixth graders' opinion essay writing. Over 12 weekly 90-min lessons, two groups of 48 and 39 students received, respectively, planning and sentence-combining instruction, which followed the Self-Regulated Strategy Development (SRSD) model. These intervention groups were compared with a practice control group of 39 students receiving standard writing instruction. The following main findings were noteworthy: (a) planning and sentence-combining instruction enhanced planning and sentence-construction skills, respectively; (b) both interventions increased opinion essay quality and text length; (c) planning instruction enhanced not only discourse-level writing but also some sentence- and word-level aspects of composition; (d) sentence-combining instruction enhanced not only sentence- and word-level writing but also some discourse-level aspects of composition; (e) after instruction, there was a correlation between self-efficacy and writing quality in both intervention groups; and (f) planning, but not sentence-combining, instructional effects generalized to summary writing. © 2013 Elsevier Inc.